Doctor Sangrado curing John Bull of repletion - with - the kind Offices of young Clysterpipe & little Boney. - - Gillray, James, 1756-1815 (Humphrey, H., 1803)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Clyster pipe; John Bull (Symbolic character); Napoleon I, Emperor of the French, 1769-1821; Fox, Charles James, 1749-1806; Sheridan, Richard Brinsley, 1751-1816; Liverpool, Charles Jenkinson, Earl of, 1727-1808 ?